Comparing Different Facets of the Social Integration of High-Achieving Students in Their Classroom: No Gender Stereotyping, but Some Nonlinear Relationships - Neuendorf, Claudia; Jansen, Malte (Journal of educational psychology, 2023)
Prior research has found that student achievement is positively related to students' social standing in class. However, negative stereotypes about high academic achievers prevail among secondary school students, suggesting that higher achievers might be less well-integrated socially. These stereotypes especially target academically high-achieving boys, students achieving highly in mathematics and sciences, and students performing well in opposite-gender stereotyped subjects. This article tries to link these stereotypes to actual social integration measured by self-report and social network nominations. It tests whether there is a nonlinear relationship between achievement and social integration, and whether high performance in opposite-gender stereotyped ways is associated with lower levels of social integration. Using data from a German large-scale assessment study with about 45,000 ninth-grade students, we investigated the relationship between achievement and multiple facets of social integration (friendship, acceptance, contact, and subjective integration). Overall, the relations between achievement and social integration were positive. Only the facet of friendship followed the hypothesized shape of an inverted U. We found no support for an interaction between general achievement level and gender and no interactions between subject of achievement and gender, except for the facet of acceptance (being asked for help by peers). Girls were asked for help more often than their male classmates, and this gender difference was particularly evident in students who were not as highly achieving. We conclude that high-achieving students are not at a higher risk for social exclusion and that stereotypes seem not to align with actual social relationships in secondary school classes in Germany.